2022
DOI: 10.1021/acs.estlett.2c00789
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Processes of Submicrometer Plastics Affecting Submerged Plant Growth in a Chronic Exposure Microcosm

Abstract: Laboratory microcosms were designed to investigate the chronic influence of sedimental submicrometer plastics (sMPs) on the growth of an aquatic submerged plant, Vallisneria denseserrulata, and the involved microbiological processes. A dose− response experiment (0−1000 μg/g) showed that the growth of V. denseserrulata was not affected by 8-week exposure to sedimental sMPs (100 and 1000 nm) until the dose reached 1000 μg/g (i.e., 0.1% w/w) in wet sediment. The observed-effect dosage of 0.1% w/w sMPs significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In this study, the high concentration of NPs significantly decreased the petiole diameter by 30%. Similar results were also obtained for the root diameter and volume of barley were reduced (exposed to 100 mg L −1 polystyrene NPs), 57 the plant height of Vallisneria denseserrulata was decreased (exposed to 1000 μg/g polystyrene NPs), 18 and the shoot length of Myriophyllum spicatum was reduced (exposed to the 3% sediment dry weight of polystyrene NPs). 14 Detrimental environmental conditions can significantly impact the metabolic state and energetic balance of photosynthetic organisms.…”
Section: Exposure To Nps Induces Changes In Morphological and Physiol...supporting
confidence: 80%
See 3 more Smart Citations
“…In this study, the high concentration of NPs significantly decreased the petiole diameter by 30%. Similar results were also obtained for the root diameter and volume of barley were reduced (exposed to 100 mg L −1 polystyrene NPs), 57 the plant height of Vallisneria denseserrulata was decreased (exposed to 1000 μg/g polystyrene NPs), 18 and the shoot length of Myriophyllum spicatum was reduced (exposed to the 3% sediment dry weight of polystyrene NPs). 14 Detrimental environmental conditions can significantly impact the metabolic state and energetic balance of photosynthetic organisms.…”
Section: Exposure To Nps Induces Changes In Morphological and Physiol...supporting
confidence: 80%
“…Adsorption and disturbance of NPs by root hairs can affect the plant basic metabolism 53 and ultimately lead to a reduction in biomass. Similar appearances were detected among Arabidopsis thaliana, 54 Lemna minor, 21 and Vallisneria denseserrulata 18 exposed to micro/nanoplastics. A concentration of >1000 mg L −1 of micro/nanoplastics significantly increased shoot biomass by 21%.…”
Section: Exposure To Nps Induces Changes In Morphological and Physiol...supporting
confidence: 77%
See 2 more Smart Citations
“…This is inconsistent with the prediction of the Anna Karenina principle, which suggested that the microbiome of diseased hosts may display greater compositional or functional variation compared to healthy ones (Arnault et al, 2023 ). Environmental perturbations such as pathogen invasion could lead to the development of new niches, and microbes nearby could then colonize the rhizosphere opportunistically, resulting in higher beta diversity (Macke et al, 2017 ; Yu et al, 2020 ; Lin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%